2012
DOI: 10.1038/jp.2011.147
|View full text |Cite
|
Sign up to set email alerts
|

Persistent cerebral blood flow by transcranial Doppler ultrasonography in an asphyxiated newborn meeting brain death diagnosis: case report and review of the literature

Abstract: We want to illustrate the difficulty of establishing a brain death diagnosis in newborn children and how an easy and useful tool, the transcranial Doppler ultrasonography, can leave an unexpected result that complicates the process despite the rest of the diagnostic tests. We describe a 36-week gestation newborn male who was diagnosed of brain death after asphyxiated and offered for donation. After initial stabilization at admission, we established brain death diagnosis by checking and meeting every criterion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In addition, due to unilateral supratentorial lesions, cases will occur in which 1 large vessel will demonstrate a CCA pattern on TCD without this occurring in the contralateral vessel. 39 In addition, abnormalities of the cranium, primarily manifested by postsurgical procedures such as decompressive hemicraniectomy 24,25 or external ventricular device placement, 24 or the more malleable cranium of infants and young children, 23 will lead to decreased sensitivities. The most likely mechanism for this was increased pulsatile arterial blood flow introduced by relief of intracranial pressure.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, due to unilateral supratentorial lesions, cases will occur in which 1 large vessel will demonstrate a CCA pattern on TCD without this occurring in the contralateral vessel. 39 In addition, abnormalities of the cranium, primarily manifested by postsurgical procedures such as decompressive hemicraniectomy 24,25 or external ventricular device placement, 24 or the more malleable cranium of infants and young children, 23 will lead to decreased sensitivities. The most likely mechanism for this was increased pulsatile arterial blood flow introduced by relief of intracranial pressure.…”
Section: Limitationsmentioning
confidence: 99%
“…The Cochrane Central data base search retrieved no additional studies. Full-text versions of these 36 studies were obtained, and 14 studies were excluded for the following reasons: 1) They did not offer a comparison criterion standard clinical examination, [12][13][14] 2) the exact number of patients could not be extrapolated from the methodology or results for analysis, 15,16 3) the study consisted of an exclusively pediatric population, 17-20 4) the article was a single-patient case report, [21][22][23] or 5) the study primarily focused on TCD analysis in populations with structural defects of the cranium (ie, patients with external ventricular devices or postdecompressive hemicraniectomy). 24,25 In the final presentation of the literature search results, there was no conflict or disagreement between 2 reviewers (J.J.C.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…This is why the determination of BD should be approached cautiously in newborns: Patent fontanels and nonfusion of the cranial sutures may prevent ICP from rising to high enough levels to produce cessation of brain perfusion. 71 Vicenzini et al reported the case of a 56-year-old woman determined BD after an intracerebral hemorrhage followed by a decompressive craniectomy. 72 Transcranial Doppler (TCD) ultrasound showed a persistence of intracranial blood flow, despite an isoelectric EEG.…”
Section: Persistence Of Brain Perfusion Despite No Clinically Detectamentioning
confidence: 99%
“…Further increases in ICP may lead to "systolic spikes" which are seen when the ICP reaches the systolic blood pressure. 31,32 Finally, it is possible to have complete absence of flow and waveform when the ICP value exceeds systolic blood pressure. The presence of either retrograde diastolic blood flow, systolic spikes, or absence of flow documented by transcranial Doppler ultrasound is said to be diagnostic of cerebral circulatory arrest.…”
Section: Transcranial Doppler Ultrasoundmentioning
confidence: 99%
“…One such patient satisfied clinical brain death but persistent flow on transcranial ultrasound delayed the diagnosis of brain death and subsequent organ donation. 32 Cerebral blood flow may still be detected in clinically brain-dead patients with open skulls or with anoxia as the cause of death. 35 There have also been several false positives in the literature where reversal of diastolic flow was observed during increased ICP.…”
Section: Transcranial Doppler Ultrasoundmentioning
confidence: 99%